High electromagnetic absorption ratio in TiB2/AZ80 composite. (January 2023) - Xu, Z.Y.; Fang, C.F.; Wang, R.; Zhang, X.P.; Feng, J.T.; Wang, Y.M.
Abstract: TiB2 /AZ80 Mg matrix composite containing particle rich zone (PRZ) and particle free zone (PFZ) was parpred by simple stiring casting and cross-rolling. The percolation structure of the PRZ endows the composite with local metamaterial properties, which introduces a new electromagnetic wave (EMW) absorption mechanism, namely plasma oscillation, for Mg matrix composite. Likewise, the multiple internal reflection and the TiB2 –Mg interface polarization also contribute to the high EMW absorption capacity. As a result, the electromagnetic interference (EMI) shielding performances measured by vector network analysis shows that the X-band EMI shielding performance of the as-rolled composite is significantly improved than that of the AZ80 alloy, especially its absorption shielding efficiency ratio exceeds 70%. Graphical abstract: Image 1 Highlights: A new EMW absorption mechanism is introduced into magnesium matrix composite. The synergistic effect of multiple EMW absorption mechanisms endows composite superior EMI shielding performance. TiB2 /AZ80 composite shows EMI shielding mechanism mainly absorbing EMW.